1993
DOI: 10.1111/j.1365-2958.1993.tb01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli hha mutants, DNA supercoiling and expression of the haemolysin genes from the recombinant plasmid pANN202‐312

Abstract: The hha gene of Escherichia coli was identified as modulating the expression of the haemolysin (hly) genes encoded by the recombinant plasmid pANN202-312. hha mutants harbouring plasmid pANN202-312 showed increased haemolysin production. The product of the hha gene, the Hha protein, shows strong homology to the YmoA protein of Yersinia enterocolitica, which plays a role in the thermoregulation of various Y. enterocolitica virulence genes. We show in this study that the Hha protein modulates the expression of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 31 publications
(8 reference statements)
3
62
0
Order By: Relevance
“…1). Deletion of hlyR results in an unnatural repression of hemolysin expression (4,42). This phenotype could be interpreted as being caused by the loss of the above mentioned ops element, but this has not yet been demonstrated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). Deletion of hlyR results in an unnatural repression of hemolysin expression (4,42). This phenotype could be interpreted as being caused by the loss of the above mentioned ops element, but this has not yet been demonstrated.…”
mentioning
confidence: 99%
“…In addition to this as yet unclear antitermination mechanism, the hly operon is regulated by both temperature and osmolarity (29,30). Studies focused on the regulatory features of the hly operon of plasmid pHly152 led to the identification of the Hha protein (4,33) and to the finding that hha mutants are partially derepressed under conditions involving temperature-and osmolarity-mediated hemolysin repression. The Hha protein belongs to a new family of modulators, which includes, among others, the YmoA protein, a temperature-dependent modulator of the expression of different virulence factors in Yersinia enterocolitica (5).…”
mentioning
confidence: 99%
“…The YmoA protein is a temperature-dependent modulator of different virulence genes, and it has been suggested that it may have a role in DNA topology (5). In fact, we have recently reported that the hha mutation increases hemolysin expression through changes in the DNA topology (3). In this work, we describe a 220-bp DNA sequence within hlyC which modulates hly transcriptional expression possibly by its interaction with the Hha protein, either directly or through Hha interaction with some other protein(s).…”
mentioning
confidence: 99%
“…These proteins, which share an 82% amino acid identity, modulate the expression of virulence factor genes. The pleiotropic phenotypes exhibited by hha and ymoA mutants include altered plasmid supercoiling [11] and increased IS transposition [12,13]. Both of these properties, which are reminiscent of those of the E. coli hns mutants, suggested that Hha and YmoA are a distinct family of nucleoid associated proteins that modulate bacterial gene expression [12,13].…”
Section: Hha-like Proteins: a Distinctive Regulatory Element Of The Ementioning
confidence: 99%
“…Studies on the mechanism of action of the Hha protein are based on the Hha-mediated environmental down-regulation of the hlyCABD operon in E. coli, which encodes the toxin α-haemolysin [9,11]. Hha does not bind directly to specific DNA sequences of the hlyCABD operon.…”
Section: Hha-like Proteins: a Distinctive Regulatory Element Of The Ementioning
confidence: 99%